Possible Drug–Herb Interaction between Herbal Supplement Containing Horsetail (Equisetum arvense) and Antiretroviral Drugs: Report of 2 Cases. (January 2017) - Cordova, Ezequiel; Morganti, Laura; Rodriguez, Claudia
The use of alternative medicines, including herbs, is common among HIV-positive patients, even in those on antiretroviral treatment. Equisetum arvense, known as "horsetail, " is mainly used for its diuretic properties. There are limited data about the pharmacological properties of this compound and the potential drug–herb interactions. The authors report 2 cases in which a possible drug–herb interaction may have led to virological breakthrough in patients who were maintained on the same regimen for many years, including lamivudine (3TC)/zidovudine (ZDV)/efavirenz (EFV) and emtricitabine (FTC)/tenofovir (TDF)/EFV, respectively. Therefore, a drug–herb interaction may be expected when these agents are taken concurrently. Until additional data are available, the authors advise clinicians to avoid this combination when possible.